[Final accepted version, unedited] Success of Fourteen Days Triple and Quadruple Therapy for the Control of Helicobacter Pylori Infections in District Kohat - Syed Fahim Shah; Sohail Aziz Paracha; Somaid Iqbal; Sadir Zaman; Aisha Gul; Iqbal Muhammad; Mudassir Hussain; Waheed Ullah (AboutScience Srl, 2022)
Background: Helicobacter Pylori is the important medical pathogen, reporting in more than half of the world population. Its infections lead to gastric inflammation, peptic ulcer and sometime cause gastric cancer. Various treatment regimes are in use for the eradication of H.pylori, but due to the emergence of antibiotic resistance, its management is a big issue for clinicians. Methodology: In current study all suspected cases that has visited District Head Quarter Hospital Kohat, were consider for screening of H. pylori infections. Preliminary information about their age, gender; general health conditions, occupation etc were taken for consideration. After recording initial sign and symptoms, samples were considered for H. pylori detections using stool antigen test and endoscopy.  A Fourteen days proton-pump inhibitor(ppi) base triple and quadruple therapies were administered to each patient comprising of Esomeprazole 40mg, Rebeprazol 20mg, Metronidazole 500mg, Levofloxacin 500mg and Bismuth subcitrate. Results: In total (n=178) positive patients, there were high numbers of positivity in patients aged below 30 years 82 (45.5%) most of which belonged to the rural areas. The MEL were given to 100patients, out of which, 88(88%) patients show successful eradication followed by the bismuth based quadruple therapy (MELB) which were given to (n=25) patients, of which 21(84%) show successful eradication.  Conclusion: This study conclude that there were high number of positive patients in aged below 30 years in which many patients were from rural area and according to this study the MEL is the most effective treatment regime for the eradication of H.pylori